Photophobia and migraine outcome during treatment with galcanezumab - Schiano di Cola, Francesca; Ceccardi, Giulia; Bolchini, Marco; Caratozzolo, Salvatore; Liberini, Paolo; Padovani, Alessandro; Rao, Renata (Frontiers in Neurology, 2023)
Background Calcitonin gene-related peptide (CGRP) plays a pivotal role in migraine physiology, not only regarding migraine pain but also associated symptoms such as photophobia. The aim of the present study was to assess monoclonal antibodies targeting CGRP efficacy not only in terms of headache and migraine frequency and disability but also in reducing ictal photophobia. Material and methods This is a retrospective observational study, conducted at the Headache Center–ASST Spedali Civili Brescia. All patients in monthly treatment with galcanezumab with at least a 6-month follow-up in September 2022 with reported severe photophobia during migraine attacks were included. Data regarding headache frequency, analgesics consumption, and migraine disability were collected quarterly. Moreover, patients were asked the following information regarding photophobia: (1) whether they noticed an improvement in photophobia during migraine attacks since galcanezumab introduction; (2) the degree of photophobia improvement (low, moderate, and high); and (3) timing photophobia improvement. Results Forty-seven patients were enrolled in the present study as they met the inclusion criteria. Seventeen patients had a diagnosis of high-frequency episodic migraine and 30 of chronic migraine. From baseline to T3 and T6, a significant improvement in terms of headache days (19.2 ± 7.6 vs. 8.6 ± 6.8 vs. 7.7 ± 5.7; p < 0.0001), migraine days (10.4 ± 6.7 vs. 2.9 ± 4.3 vs. 3.6 ± 2.8; p < 0.0001), analgesics consumption (25.1 ± 28.2 vs. 7.6 ± 7.5 vs. 7.6 ± 8.1; p < 0.0001), MIDAS score (82.1 ± 48.4 vs. 21.6 ± 17.6 vs. 18.1 ± 20.5; p < 0.0001), and HIT-6 score (66.2 ± 6.2 vs. 57.2 ± 8.6 vs. 56.6 ± 7.6; p < 0.0001) was found. Thirty-two patients (68.1%) reported a significant improvement in ictal photophobia, with over half of the patients reporting it within the first month of treatment. Photophobia improvement was more frequent in patients with episodic migraine (p = 0.02) and triptans responders (p = 0.03). Conclusions The present study confirms previous reports regarding galcanezumab efficacy beyond migraine frequency. In particular, over 60% of patients, in our cohort, documented a significant improvement also in reducing ictal photophobia. This improvement was, in most patients, moderate to high, and within the first 6 months of treatment, regardless of the clinical response on migraine frequency.